Morphology of WBCs on Peripheral Blood Smear of COVID 19 Positive Patients - Khandelwal, Dr Archana; Shrivastava, Rashmi; Pawar, Shubhangi; Pandey, Avantika (Annals of Pathology and Laboratory Medicine, 2021)
Background: Covid-19 pandemic has affected almost all the inhabited areas on our planet. Researchers are working hard to bring this disease to its resolution. There is emerging evidence everyday to point towards the altered parameters in our body. Complete blood picture and peripheral blood smears are also showing considerable changes. These changes can help to raise suspicion of Covid-19 infection at the earliest. This can help us in future to differentiate from diseases with similar findings on peripheral blood smear. Methods: This is a prospective observational study in which 500 peripheral smears of Covid-19 infected patients were observed and the findings were recorded. All the morphological changes in WBCs, total WBC count and neutrophilic lymphocyte ratio were recorded over a span of six months from June2020-December 2020. This data was analyzed statistically. Result: Our study reveals that there is not much change in WBC counts in initial stage of the disease. Increased Neutrophil Lymphocyte ratio is seen in almost all the patients as the disease progresses. Presence of toxic granules in the cytoplasm of cells of neutrophilic series was the earliest noticeable change in the morphology of WBCs. Earliest response is seen in lymphocytes as azurophilic granules in cytoplasm and large indented nuclei. Conclusion: With the above study, we can conclude that there are significant and specific changes observed in the morphology of WBCs of the affected patients. This simple and easily available test can be an effective tool in helping to raise suspicion of the infection. This in turn will lead to early diagnosis and treatment.